MANAJEMEN KESEHATAN PADA MASYARAKAT URBAN - Rumerung, Christie; Eka, Ni Gusti Ayu; Sinaga, Juniarta; Sitanggang, Yenni Ferawati; Lumbuun, Nicolaski (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Indonesia's Health Development, among others, aims to increase the awareness and ability of individuals and communities to live behavior patterns and a healthy environment. It is stated in the policy that health development requires effective and efficient efforts, resources and management in maximizing the degree of public health. Various characteristics and criteria of the community will require different health management. For example, in the late adult and elderly age categories, extra efforts and management are needed in maintaining a healthy, quality and productive life. Urban communities living in urban areas tend to have a more modern orientation of education and cultural values, but on the other hand, they face the dynamics of socioeconomic factors and environmental changes that affect the degree of well-being and individual health. One of the efforts to achieve a maximum degree of health is done through health promotion and examination. This activity has been carried out in urban and sub-urban Tangerang, involving 40 residents (10 men and 30 women) with an average age of 59.63 years. The results of blood pressure checks showed that only 11 residents were within the normal range, while the average cholesterol level was 208.39mg/dL; uric acid 7.89mg/dL; blood sugar 113.65mg/dL. This Community service activity recommends continuous and structured health checks in order to help achieve the degree of community health.